INTEGRASI PASAR KAKAO INDONESIA - Amzul Rifin; Fitri Nurdiyani (Departemen Agribisnis, FEM-IPB, 2007)
Indonesia is the third largest cocoa producing country in the world. The cocoa price in Indonesia refers to the world price. This paper examines the efficiency of world’s cocoa price that is transmitted to cocoa price in Indonesia and in major cocoa producing provinces, such as North Sumatera, South Sulawesi, Central Sulawesi, South East Sulawesi and North Sulawesi. The efficiency of the transmission can be calculated by testing the cocoa’s market integration using two indicators, i.e. short market segmentation and short-run integration. The result showed that the cocoa market in Indonesia was segmented and not integrated with the world market. The cocoa markets in North Sumatera and Central Sulawesi were segmented with the world market, but other provinces were not. On the other hand, only the cocoa market in North Sumatera was integrated in short-run with the world market.